Customer Relationship Marketing Sebagai Mediasi Penetapan Harga, Kemasan Unik dan Desain Tata Letak Terhadap Minat Berkunjung Ulang Konsumen MIXUE Indonesia - Isti Riana Dewi; Amroni Amroni; Dewi Laily Purnamasari; Siska Viora; Fifi Julianti (Universitas Muhammadiyah Tangerang, 2023)
The development of the food and beverage business in Indonesia has improved after the Covid-19 pandemic. The development of the food and beverage business can be seen from the market expansion carried out through the number of outlets. Mixue is a newcomer that has successfully competed in controlling the market through the spread of its outlets. Several strategies are designed to dominate the market such as pricing, unique packaging and layout design. The rapid development raises several problems that occur. However, this problem did not affect Mixue's sales, which were increasingly crowded. This study aims to determine the effect of price, unique packaging, and layout design on the intention to revisit at Mixue Indonesia outlets. As well as the role of customer relationship marketing as a mediation between price, unique packaging, and layout design on the interest to revisit Mixue Indonesia outlets. The research sample is Mixue Indonesia customers. This research method uses the Partial Least Square (PLS) tool. The findings from this study are that price, unique packaging, and layout design influence the intention to revisit at Mixue Indonesia outlets. As well as customer relationship marketing as mediation between price, and unique packaging to interest in revisiting at Mixue Indonesia outlets is supported however, layout design is not supported.